Viral Diseases of Poultry in Assam, India: A Review - Ahmed, Rofique; Deka, Pubaleem; Hazarika, Ritam; Barua, Jonmoni; Sharma, Abhilasha; Sarma, Jayashree; Devi, Bandana; Das, Sangeeta; Nath, Mrinal Kumar; Das, Gunajit; et al. (International Journal of Bio-resource and Stress Management, 2022)
The Indian poultry market is estimated to have an annual growth rate of 8.1% as of today. However, infectious diseases in poultry pose an important constraint in the growth and development of this sector in our region. Among infectious diseases, viral diseases of poultry pose a serious threat to the poultry industry from an economic point of view. Several viral disease outbreaks have been reported by various researchers from different parts of the country. Among the common viral diseases of poultry, incidences of Newcastle disease, Avian Influenza, Fowl Pox, Infectious Bursal Disease, Marek’s disease, Infectious Bronchitis, Infectious Laryngotracheitis and Inclusion Body Hepatitis are significant in Assam as well as other parts of India. Thorough epidemiological studies followed by the identification of different serotypes, pathotypes, strains, etc. by genotyping and molecular characterization of viral disease pathogens may lead to ways to control and eradicate the diseases. Importance should be given to maintaining basic preventive measures like biosecurity, farm hygiene, and proper vaccination. In a developing country like India, disease outbreaks can impact the country’s economy. In this study, a brief view of the common viral disease of poultry and its diagnosis and control strategies in Assam, India is depicted. However, this review well indicates a plethora of avian diseases that have occurred over the years causing a severe impact on poultry farming as a whole.